Mobile applications in medical education: A systematic review and meta-analysis. - Viji Pulikkel Chandran; Athira Balakrishnan; Muhammed Rashid; Girish Pai Kulyadi; Sohil Khan; Elsa Sanatombi Devi; Sreedharan Nair; Girish Thunga (PLoS ONE, 2022)
Objective This review evaluates the effectiveness of smartphone applications in improving academic performance and clinical practice among healthcare professionals and students. Methods This study followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Articles were retrieved from PubMed, Scopus, and Cochrane library through a comprehensive search strategy. Studies that included medical, dental, nursing, allied healthcare professional, undergraduates, postgraduates, and interns from the same disciplines who used mobile applications for their academic learning and/or daily clinical practice were considered. Results 52 studies with a total of 4057 learner participants were included in this review. 33 studies (15 RCTs, 1 cluster RCT, 7 quasi-experimental studies, 9 interventional cohort studies and 1 cross-sectional study) reported that mobile applications were an effective tool that contributed to a significant improvement in the knowledge level of the participants. The pooled effect of 15 studies with 962 participants showed that the knowledge score improved significantly in the group using mobile applications when compared to the group who did not use mobile applications (SMD = 0.94, 95% CI = 0.57 to1.31, P<0.00001). 19 studies (11 RCTs, 3 quasi-experimental studies and 5 interventional cohort studies) reported that mobile applications were effective in significantly improving skills among the participants. Conclusion Mobile applications are effective tools in enhancing knowledge and skills. They can be considered as effective adjunct tools in medical education by considering their low expense, high versatility, reduced dependency on regional or site boundaries, online and offline, simulation, and flexible learning features of mobile apps.